Comparative analysis of the use of PTV VISSIM 9.00 & Synchro 11 in an intersection with high freight transportation traffic - Chavarria, Aguilar (2024)
This scientific article presents the application of the PTV VISSIM 9.00 software & the Synchro 11 software as a comparison mode for the analysis of an intersection, focusing on heavy-duty vehicles circulating at the intersection of two avenues, which are the main problem of an industrial and commercial area. The purpose of the article is to improve the traffic management of an intersection through a redesign of the roads and optimize the traffic light cycles of the study area, obtaining better saturation flows and a reduction in the queue length of the vehicles. at an intersection affected by freight traffic. With the comparison of the data obtained in the current situation and proposed in both software's, it is concluded that the PTV VISSIM 9.00 software is the most suitable for the application in a complicated intersection. The redesign proposal at the intersection and the implementation of the proposed traffic light timings in the PTV VISSIM 9.00 software were effective in reducing the length of vehicle queues and improving service levels. Demonstrating that the PTV Vissim 9.00 software is more convenient to model the problematic chaotic intersection compared to the Synchro 11 software.